Imaginary place in Atta Muhammad’s novels - Rahman Sofi, Kawa; Muhammad Saeed, Azad (Zanco Journal of Human Sciences, 2023)
Imaginary place has great significance in novels, not only because it is one of the artistic elements, or it is the place that the events happen in it, but the reason is that the place in novel is imaginary place “fictition”,it is either established on reality, that has roots in realife or It is built on dreams or imagination far from reality, which has no opportunity to appear in the reality, the place in novel is not the same place that exists outside, the novelist indices to the real place that exists outside by indication and signals to make the reader believe that the place is Same real place. Surely, the place in novel is an imaginary place” fictition” it is built through language, and it is uploaded by the ideas the psychology of the novelist opinions. the novelist makes up familiar to several places that are different from reality, which are existed inside in imagination world.